Neutrophil CD64 can be an early predictor for sepsis during febrile neutropenic episodes in children with cancer: a case control study - Marwa Zakaria; Nehad Karam; Tamer Hassan; Nahla Zidan; Asmaa Abdelsalam; Raghdaa A. Ramadan; Marwa L. M. Rashad; Eman Abdelaziz; Ahmed Ramadan; Ahmed A. Ali (Italian Journal of Pediatrics)
Abstract Background Febrile neutropenia (FN) is a common treatment-related complication in pediatric cancer patients with substantial morbidities and mortalities. Previous studies reported that neutrophil CD64 (n CD64) had higher diagnostic accuracy for infection with high sensitivity and specificity in neonates, pediatrics and adult patients. We aimed to evaluate the usefulness of neutrophil CD64 expression as an early diagnostic marker of sepsis in children with cancer during episodes of FN. Methods a case control study was conducted on 100 children (50 patients with hematological malignancies and febrile neutropenia, 25 patients with hematological malignancies without febrile neutropenia and 25 apparently healthy children as a control group). Routine laboratory investigations including blood culture were done in patients with cancer according to our local standards. Procalcitonin level and Neutrophil CD64 expression by flowcytometry were measured for all study participants. Results n CD64 expression was significantly higher in patients with cancer and FN compared to other groups (p > 0.001). At a cutoff value of ≥ 17.82%, serum n CD64 had 94% sensitivity and 72% specificity. n CD64 expression level was negatively correlated to absolute neutrophil count (ANC) during episode of FN (r= (-0.359, p = 0.01). A positive correlation was found between nCD64 expression and both of CRP and procalcitonin. Blood culture was positive in 54% in patients with cancer and FN. The most common isolated organism was Kllibselia pneumonia. Among patients with cancer and FN, n CD64 expression level was significantly higher in patients with positive blood culture compared to those with negative cultures. Conclusion Neutrophil CD64 expression seems to be a reliable marker in early detection of sepsis during episodes of febrile neutropenia in children with hematological malignancies.